Retro-pancreatic pull-through reconstruction of the hypoplastic portal vein using the autologous mesosystemic shunt vessel in adult living donor liver transplantation: a case report - Shinsuke Sugenoya; Atsuyoshi Mita; Akira Shimizu; Yasunari Ohno; Koji Kubota; Yuichi Masuda; Tsuyoshi Notake; Yuji Soejima (Surgical Case Reports, 2024)
Abstract Background In liver transplant patients with hypoplastic portal vein (PV), when the narrowed segment is extended too deep into the dorsal side of the pancreas, it is difficult and dangerous to reconstruct the interposition graft from the upper part of the pancreas. Herein, we present a case of PV reconstruction with the autologous mesosystemic shunt vessel from the caudal side of the pancreas in a situation where the narrowed PV was deep, and we discuss the technical details. Case presentation A 25-year-old woman presented with cholestatic liver cirrhosis due to biliary atresia after Kasai procedure. Since her jaundice progressed, she was referred to our hospital for liver transplantation. Laboratory tests showed that her total bilirubin was elevated to 7.6 mg/dL. The Model for End-Stage Liver Disease score was 18, and the Child–Pugh score was 9 (Grade B). She underwent living donor liver transplantation (LDLT) using a right hemi-liver graft procured from her 54-year-old mother. The conventional approach from the cephalad side to the superior mesenteric vein (SMV) and splenic vein (SpV) confluence behind the pancreas was extremely difficult in this case because the confluence of SMV and SpV was close to the lower edge of the pancreas. Therefore, we decided to perform PV reconstruction from the caudal side. The main trunk of PV was documented as narrow (5 mm in diameter), for which retro-pancreatic pull-through PV reconstruction was successfully performed using her own mesosystemic shunt vessel. A contrast computed tomography (CT) scan was performed on postoperative day 5 because of an elevation of D-dimer and found a partial thrombus in the left pulmonary artery, as well as in the PV and left renal vein. Thereafter, thrombolytic therapy with low-molecular-weight heparin was started immediately and switched to a direct oral anticoagulant. The follow-up CT taken 3 months after liver transplantation revealed a patent PV without thrombus; therefore, anticoagulant therapy was discontinued. Currently, the patient has been well and active with a patent PV without anticoagulant therapy for 3 years after LDLT. Conclusions Retro-pancreatic pull-through reconstruction of the hypoplastic PV is a feasible and effective method when conventional reconstruction is not indicated.